Influences of growth substrates and oxygen on the electron transport system in Acinetobacter sp. HO1-N. - Ensley, B D (1980)
The electron transport system of Acinetobacter sp. HO1-N was studied to determine the specific cytochromes and to measure changes in the composition of the respiratory system due to growth in various concentrations of oxygen or types of growth substrates. Spectrophotometric analysis revealed that the quantity and types of cytochromes changed in response to growth under various concentrations of oxygen. Growth on alkane and nonalkane substrates resulted in only minor differences in cytochrome composition or oxidase activities. Membranes prepared from cells grown under oxygen-limiting conditions contained at least one b-type cytochrome, cytochrome o, cytochrome d, and slight traces of cytochrome a1, whereas membranes prepared from cells grown in the presence of high oxygen concentrations contained only low levels of cytochromes b and o. Polarographic measurements, electron transport inhibitor studies, and photoaction spectrum analyses indicated that cytochromes o, a1, and d were potentially capable of functioning as terminal oxidases in this organism. These experiments also revealed that all three cytochromes may be involved in the oxidation of reduced nicotinamide adenine dinucleotide, succinate, or N,N,N',N'-tetramethyl-p-phenylenediamine.